FRI0673 Do patient reported outcome measurement information system (PROMIS) computer adaptive tests correlate with disease activity in juvenile idiopathic arthritis?. (12th June 2018) - Trachtman, R.; Murray, E. T.; Szymonifka, J.; Adams, A. B.; Pan, N.; Taber, S. F.; Onel, K. B.; Mandl, L. A.
Abstract : Background: The importance of patient-reported outcomes is increasingly recognized both in clinical care and in research. PROMIS is an NIH-supported collection of patient-reported outcome measures, covering a variety of domains that are designed without disease specificity. While 'short forms' have been studied in juvenile idiopathic arthritis (JIA), PROMIS computer adaptive tests (CATs) have not. Objectives: This study evaluates whether PROMIS CATs correlate with disease activity in patients with JIA. Methods: A convenience sample of patients with JIA (N=21) were recruited from a single center. Patients aged 10–17 years completed all available pediatric PROMIS CATs, and parents of patients aged 2–9 years completed all available parent proxy PROMIS CATs (fatigue, pain interference, peer relations, anxiety, depressive symptoms, and mobility). Correlation of the CATs t-scores with disease activity, as measured by the Juvenile Disease Activity Score-71 (JADAS-71), (0–101, higher being worse) was evaluated using Spearman correlation coefficients. Results: All families approached completed the PROMIS CATs: 13 patients and 8 parents (table 1). Median age was 12.7 years (range 1.3 – 18.6 years), and mean JADAS-71 score was 9.58 (SD 2.07). 69% of patients completed PROMIS CATs remotely via smartphone. Anxiety (r=0.74, p=0.006), depressive symptoms (r=0.84, p<0.001), and pain interference (r=0.64, p=0.018) CATs correlated strongly with JIA disease activity (table 2). Among parent proxy CATs, only anxiety correlated with disease activity (r=0.71); however the association was not statistically significant. Conclusions: Our results demonstrate that the PROMIS CATs are feasible to administer in an outpatient pediatric rheumatology setting. Anxiety, depressive symptoms, and pain interference were significantly correlated with disease activity, even though mean disease activity was relatively low. This underscores the negative effect on quality of life of even mild disease. Parent proxy CATs showed poor correlations with disease activity, suggesting parents are inaccurate in assessing important aspects of their child's health. Larger prospective studies are needed to evaluate the sensitivity of PROMIS CATS to change in disease activity over time. Disclosure of Interest: None declared